Hubungan Indeks Massa Tubuh Dengn Osteoartritis Lutut Pada Pasien Di Klinik Singgasana Rama Blitar - Arintika, Andis Puspita; Halimah, Nurul; Wardoyo, Puspo; Pradipta, Angria (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: This study aims to determine the relationship between body mass index and knee osteoarthritis in patients at Singgasana Rama clinic, BlitarMethods: The method used in this research is descriptive observational with purposive sampling. The data obtained from the survey results include gender, age, occupation. With a statistical correlation test, and the measuring instrument that been used is WOMAC scale.Results: From the study of 55 people that fulfill the inclusion criteria got the result  that there are 11 people with body mass index of 18.5-25(20%), 8 people with 25.1-27 (14.54%), 36 people with >27 (65,45%). Meanwhile their WOMAC score there are 6 people with 0-40%, 33 people with 41-70%, 16 people with more than >70%. The result  of correlation test between body mass index (X) and WOMAC (Y) score  is 0,00<0,05 which mean H0 is rejected  and there are significant relation between body mass index (X) and WOMAC (Y) score. Pearson correlation score 0,0558 higher than r table 0,261 which mean there is huge relation between the two variable.Conclusion: body mass index have significant relation with knee osteoarthritis, which mean the higher body mass index is the higher the risk someone will get knee osteoarthritis.